Intelligent colorimetric film incorporated with anthocyanins-loaded ovalbumin-propylene glycol alginate nanocomplexes as a stable pH indicator of monitoring pork freshness. (30th January 2022) - Zhang, Xinyue; Zou, Wenjie; Xia, Minquan; Zeng, Qi; Cai, Zhaoxia
Highlights: ACNs-loaded OVA-PGA nanocomplex was added into the film as a stable pH indicator. Intelligent film was designed with ACNs-loaded OVA-PGA nanocomplexes and PG matrix. Hydrogen bond improved intelligent film (PG/ACNs-loaded OVA-PGA) properties. PG/ACNs-loaded OVA-PGA film was sensitive to pH 2–11 buffers and volatile ammonia. The pH-responsive intelligent film changed color in pork freshness monitoring. Abstract: Protein-polysaccharide nanocomplexes system could improve the low stability of ACNs, making ACNs become a potential and stable pH indicator. In this study, intelligent colorimetric film was designed to monitor pork freshness by incorporating ACNs-loaded ovalbumin-propylene glycol alginate nanocomplexes (ACNs-loaded OVA-PGA) into polyvinyl alcohol/ glycerol (PG) matrix. The intelligent film (PG/ACNs-loaded OVA-PGA film) presented well barrier performance (lower water vapor permeability and light transmittance at 200–600 nm). Fourier transform infrared spectroscopy further confirmed the hydrogen bonds among film-forming components. Moreover, Scanning electron microscope and X-ray diffraction showed that ACNs-loaded OVA-PGA was uniformly distributed in film matrix but decreased the crystallinity of polyvinyl alcohol. PG/ACNs-loaded OVA-PGA film had distinguishable colorimetric response to pH 2.0–11.0 buffers and volatile ammonia. In the test, PG/ACNs-loaded OVA-PGA film displayed visible color alterations from purplish-red to dark-blue as pork freshness decreased, suggesting it can be used in intelligent packaging for real-time monitoring freshness of meat products.